2001
DOI: 10.1046/j.1524-4741.2001.20038.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Lesions After Tamoxifen Therapy in Breast Cancer Women

Abstract: Tamoxifen, a nonsteroidal antiestrogen with a partial estrogen-antagonist activity, is widely used as a hormonal adjuvant therapy for breast cancer in women with positive receptors for estrogens. Its prolonged administration has been associated with a series of collateral effects, among which the endometrial carcinoma is the most important. The aim of our study was to investigate an eventual correlation between a therapy with tamoxifen and the onset of endometrial lesions. We recruited 228 postmenopausal patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…It has been shown to prevent breast cancer in high‐risk women 40 . Although tamoxifen has antiestrogenic effects on breast tissue, it has a positive estrogenic effect on the postmenopausal endometrium and myometrium and results in an increased number of uterine and endometrial abnormalities 41 , 42 41 .…”
Section: Abnormal Uterine Bleeding In the Breast Cancer Patientmentioning
confidence: 99%
“…It has been shown to prevent breast cancer in high‐risk women 40 . Although tamoxifen has antiestrogenic effects on breast tissue, it has a positive estrogenic effect on the postmenopausal endometrium and myometrium and results in an increased number of uterine and endometrial abnormalities 41 , 42 41 .…”
Section: Abnormal Uterine Bleeding In the Breast Cancer Patientmentioning
confidence: 99%
“…Demgegenüber zeigten andere Studien kein signifikant erhöhtes Risiko oder fanden vornehmlich Niedrig-Risiko-Karzinome (Maugeri et al, 2001;Nishimura et al, 2001). …”
Section: Nachfolgend Sollen Die Wichtigsten Risikofaktoren Näher Erläunclassified
“…A higher incidence of endometrial alterations, such as polyps, hyperplasia, carcinoma and sarcoma, have been reported in menopausal tamoxifen users, in addition to an increased risk of endometrial malignant neoplasms (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Among the endometrial alterations reported in tamoxifen users, polyps are the most common, with a prevalence of 13-30% (10,12,15,16). In patients treated with tamoxifen, microscopic analysis revealed that polyps are more translucent, edematous and fibrotic, with less stromal cellularity (10).…”
Section: Introductionmentioning
confidence: 99%